Kontribusi Usaha Ternak Sapi Terhadap Pendapatan Anggota Kelompok Tani Suka Mulia pada Perkebunan Kelapa Sawit Rakyat - Fitrini Fitrini (Jurnal Embrio, 2012)
The aims of study is to determine the income of beef cattle’s farm enterprises and the contribution of beef cattle’s farm enterprises to members’ income of Suka Mulia farmer group in palm oil plantations. The research was conducted in the Bukit Harapan village, Merlung Sub District, from 10 November to December 2011 with a survey method. Respondents of this study are all members of Suka Mulia farmer groups. The data collected is primary data which is obtained from questionnaires and secondary data which is taken from related government institution. Data analysis was using qualitative and quantitative descriptive analysis. The results showed that the average of income of beef cattle’s farm enterprises is Rp 2.409.801/farmer/year and its contribution to group member’s income is 4.36%. This shows that the beef cattle’s farm enterprises is still a side job, however the writers recommends that beef cattle’s farm enterprises should be developed because of the integration system between beef cattle and palm oil plantations be profitable for farmers.